Reasons for living in young adults: Validation of the RFL-YA - Cassaretto, Mónica (2012)
The study analyses the psychometric properties of the Reasons for Living Inventory for Young Adults (RFL-YA) in a group of 368 university students from Lima, Peru, from both sexes and whose ages fluctuate between 16 and 30 years of age. The instruments used were the RFL-YA (Gutiérrez et al., 2002), Antonovsky’s Sense of Coherence Scale (SOC) (1993) and Hert’s Hope Scale (Arnau, Martínez, Niño de Guzmán, Herth & Yoshiyuki, 2010) in order to determine the convergent validity of the RFL-YA. Results show elevated reliability indexes. A 0.93 coefficient for the whole test and a 0.83 and 0.92 for each of the areas of the test. The factorial structure is adequate, and all 5 factors were reproduced with a 63.74% of explained variance. The correlation between the Sense of Coherence Scale and the Hope Scale resulted positive, high and significant, thus confirming the validity and reliability of the inventory for similar populations.